Knockout of p11 attenuates the acquisition and reinstatement of cocaine conditioned place preference in male but not in female mice. Issue 7 (4th May 2016) - Thanos, Panayotis K.; Malave, Lauren; Delis, Foteini; Mangine, Paul; Kane, Katie; Grunseich, Adam; Vitale, Melissa; Greengard, Paul; Volkow, Nora D.
ABSTRACT: Cocaine's enhancement of dopamine signaling is crucial for its rewarding effects but its serotonergic effects are also relevant. Here we examined the role of the protein p11, which recruits serotonin 5HT1B and 5HT4 receptors to the cell surface, in cocaine reward. For this purpose we tested wild‐type (WT) and p11 knockout (KO) male and female mice for cocaine conditioned place preference (CPP) and its cocaine‐induced reinstatement at different abstinence times, after 8 days of extinction and 28 days of being home‐caged. All mice showed significant cocaine CPP. Among males, p11 KO showed lower CPP than WT; this difference was also evident after 28 days of home‐cage abstinence. In contrast, in females there were no CPP differences between p11 KO and WT mice at any time point tested. Cocaine priming after the 28‐day home‐cage abstinence period also resulted in lower cocaine conditioned motor activity in both male and female p11 KO mice. These results suggest that cocaine CPP and its persistence during extinction and reinstatement are modulated in a sex‐differentiated manner by p11. The lack of protein p11 confers protection from CPP on male, but not female mice, immediately after cocaine conditioning as well as after prolonged abstinence, but not after short‐term withdrawal.Synapse 70:293–301, 2016. © 2016 Wiley Periodicals, Inc. Abstract : The lack of protein p11 confers protection from cocaine conditioned place preference on male, but not female mice, immediately after cocaine conditioning as well as after prolonged abstinence, but not after short‐term withdrawal.